Effectiveness of Video Method Training with Demonstration on the Competency of Basic Life Support Training Participants in the Gucialit Work Area - Usmiati Ningsih; Zainal Abidin; Widya Addiarto (Al-Hijrah Indonesia, 2026)
Background: Basic Life Support (BLS) competency is critical for improving survival rates in cardiac arrest emergencies. However, the optimal instructional method for training public service employees remains a subject of debate. Objective: This study aimed to evaluate and compare the effectiveness of video-based training versus demonstration methods on BLS competency among public service employees. Methods: A quasi-experimental study with a pre-post test design was conducted in the Gucialit Community Health Center work area in July 2025. A total of 52 participants were selected using a total sampling technique and divided into two groups: video method (n=26) and demonstration method (n=26). Competency was assessed using a structured questionnaire before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test with a significance level of α=0.05. Results: Both training methods significantly improved BLS competency. In the video group, competent participants increased from 10 (38.5%) to 24 (92.3%) (p=0.000). In the demonstration group, competency rose from 14 (53.8%) to 23 (88.5%) (p=0.003). Descriptively, the video method yielded a slightly higher post-training competence rate compared to the demonstration method. Conclusion: Both video and demonstration methods are effective in enhancing BLS competency among public service employees. The video method demonstrated a marginally higher effectiveness, suggesting it as a viable, scalable alternative for community-based training programs.